Small Incision Combined with Nephroscope Operation in the Treatment of Infectious Pancreatic Necrosis: A Single-Center Experience of 37 Patients - Yinghui Song; Guoguang Li; Hongwei Zhu; Zhangtao Yu; Bo Jiang; Chuang Peng; Sulai Liu (Gastroenterology Research and Practice)
Objective. To explore the safety and efficacy of small incision combined with nephroscope surgery in the treatment of infectious pancreatic necrosis. Methods. A retrospective analysis of the clinical data of 37 patients with infectious pancreatic necrosis who underwent small incision combined with nephroscopy in the Department of Hepatobiliary Surgery of Hunan Provincial People’s Hospital from January 2018 to December 2019. Results. All 37 patients successfully completed small incision combined nephroscope surgery. The median time from the onset to the operation of all patients was 38 days (range: 29-80 days), and the hospital stay was 19 days (range: 3-95 days). The median number of drainage tubes placed during the operation was 4 (range: 2-8). According to the different surgical approaches, 13 cases were through the retroperitoneal approach, 11 cases were through the omental sac approach, 2 cases were through the intercostal approach, and 11 cases were combined approach. The operation time was 85.3±31.6 min, and intraoperative bleeding was 63.1±40.0 ml. The incidence of complications (Clavien-Dindo grade 3 and above) was 5.4%. Among them, 2 patients were admitted to the intensive care unit due to postoperative bleeding, 1 case was cured by conservative treatment, and 1 case was cured by interventional treatment. During the follow-up period, 2 patients developed colonic fistula at 2 weeks after operation, and 2 patients developed gastric fistula at 1 week and 3 weeks after operation; all were cured by conservative treatment. Conclusion. Small incision combined with nephroscope surgery is an effective treatment for patients with infectious pancreatic necrosis by removing necrotic tissue, unobstructed drainage, and reducing complications.